Targeted Charging of Ubiquitin to E2: A new approach to study ubiquitination in cells - Hill, Caitlin. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Chemistry.; Advisor: Rebecca Scheck.; Committee: Joshua Kritzer, Krishna Kumar, and Michelle Farkas.; Keywords: Biochemistry, and Cellular biology.